Perception of Transgenders Regarding Voice Quality, Gender Identity, Anxiety and Avoidance - Ayesha Bukhari, Ghazal Awais Butt, Muhammad Usman Khalid, Hafiza Shabnum Malik, Syeda Mariam Zahra, Anum Amin (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Any person who deviates from the social norm of binary gender is considered to be transgender. People who identify as transgender do not fit the gender assigned to them at birth. Aim: To determine the perception of transgender regarding voice quality, gender identity, anxiety and avoidance. Methodology: Cross sectional study was conducted in Multan transgender community. Convenience sampling technique was used. Sample size was N=83 calculated by online sample size calculator. After the inclusion and exclusion criteria a demographic Performa, TVQMtF, TVQFtM Performa was used. Results: Male to Female n= 78 mean value 27.64±7.91and Female to Male n=05 mean value 25.20±9.25. Male to female with mean value of anxiety and avoidance, gender identity and voice quality, 22.22±7.81, 17.02±4.71, 22.68±6.14 respectively.Female to male with mean value of anxiety and avoidance, gender identity and voice quality, 21.40±7.66, 15.00 ±6.32, 20.40±7.86. Conclusion: Both trans men and trans women participants experience larger levels of anxiety and avoidance, gender identification, and vocal quality difficulties. Keywords: Transgender persons, Voice Quality, Anxiety, Depression, Gender dysphoria